The effect of quality-environmental investment on horticultural firms' competitiveness - Galdeano E.; Céspedes J.J. (Food quality products in the advent of the 21st century: production, demand and public policy, 2005)
The aim of this paper is to analyse the impact that environmental respectful practices and total management quality improvements have on the firm's Competitiveness (profitability and market share) within the fresh fruit and vegetable sector. Andalusian producing-marketing entities (Producer Organisations) serve as a reference for our analysis. For these entities there are subsidy programmes aimed at developing quality and environmental practices. Such programmes are a top priority for the CAP's Common Market Organisations. An analysis of a simultaneous equations model is suggested considering the distinguishing effect of investment in quality-environment and the possible endogeneity problems among the variables. The results show a positive correlation between the application of the aforementioned activities and the Competitiveness of the horticultural firms.SN ISSN 1022-1379
83. EAAE Seminar on Food Quality Products in the Advent of the 21st Century: Production, Demand and Public Policy, 2003/09/04-07, Chania (Greece)